Manajemen Profesionalisme Guru dalam Meningkatkan Mutu Pembelajaran di MI Ma’arif NU 01 Dawuhan Wetan - Alya Mahirotun Numa; Muh. Hanif (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The development of training and professional development programs is a vital part of education management to improve the quality of teacher performance. There are a number of important aspects that must be considered in designing training and professional development programs so that their implementation is effective and on target. Objectives: This study focuses on a comprehensive analysis of how the implementation of teacher professionalism management in MI Ma'arif NU 01 Dawuhan Wetan as an effort to improve the quality of the learning process. This study aims to examine the strategies used by the madrasah in planning, implementing, evaluating, and the impact of teachers' professional competence. Through this approach, the study is expected to evaluate the extent to which teacher professionalism management contributes to the quality of learning processes and outcomes, and formulate strategic recommendations to encourage continuous efforts to improve the quality of education. This research adopts the descriptive qualitative method. The study was analyzed using in-depth interviews, observation and documentation. Data analysis followed the Miles and Huberban model including data reduction, data presentation, data condensation and formulation of final results. This study reveals that the management of teacher professionalism in improving quality is: (1) Teacher Professionalism Development Planning, (2) Implementation of Teacher Professionalism Program, (3) Evaluation and Monitoring of Teacher Professionalism, and (4) Impact on Learning Quality. Teacher professional development programs are systematic and sustainable. The implementation of well-planned professional development programs at MI Ma'arif NU 01 Dawuhan Wetan shows that the management of teacher professionalism is able to optimize the quality of teaching and the academic achievement of students. among teachers by means of internal Subject Teacher Consultation (MGMP). teacher competence through In House Training (IHT) activities, internal Subject Teacher Consultation (MGMP), and external training has proven effective in improving teacher teaching skills at MI Ma'arif NU 01 Dawuhan Wetan. Proper evaluation allows identification of areas that require development, so that training and coaching programs can be tailored to the specific needs of teachers. the existence of a reward system for outstanding teachers also increases motivation and enthusiasm in teaching.